(untitled) (Indonesian Anti Corruption Studies, 2024)
Grassroots movements have increasingly become important actors in the fight against corruption, particularly in contexts where formal institutions face limitations. This paper presents a case study of community-based monitoring initiatives in Indonesia, which empower local citizens to oversee public projects and service delivery. Through fieldwork in several districts, interviews with activists, and analysis of project outcomes, the study evaluates the effectiveness, challenges, and impact of these grassroots anti-corruption efforts. Results indicate that community monitoring fosters transparency and accountability by exposing irregularities and pressuring local officials, though it often encounters resistance from entrenched interests and lacks sufficient institutional support. The paper argues that while grassroots movements cannot substitute formal institutions, they are crucial complements that enhance civic participation and democratize anti-corruption efforts. This research adds to the international literature on participatory governance by demonstrating how localized activism can generate meaningful oversight in decentralized settings, offering practical lessons for similar initiatives globally.